SYMPOSIUM ON OPHIOLITE GENESIS AND EVOLUTION OF OCEANIC LITHOSPHERE - Searle, M (1991)
The recently published Special PublicationN o 49 of the Geological Society of London The Geology and Tectorlics of the Oman Region edited by A. H. F. Robertson, M. P. Searle and A. C. Ries (Feb. 1990) resulted largely from a six year AMOCO-funded project concentrating mainly on the structure, stratigraphy ansde dimentology of the platform margin and basin sediments beneath the Semail ophiolite. This study, and more particularly the BRGM-French project (1982-1990) formed the basis of the ophiolite conference. It was held at the Sultan Qaboos University, Sultanate of Oman, 7-18 January 1990, and was the first, major, international geological conference to be held in Oman. Over 300participants from 27 countries attended.